Karakteristik Tipe Fluida Mata Air Panas Ranolewo di Desa Toraget Kecamatan Langowan Utara Kabupaten Minahasa Sulawesi Utara - Arfian Ronaldo Sinurat; Rolles Nixon Palilingan; Sixtus Iwan Umboh (Jurnal FisTa : Fisika dan Terapannya, 2024)
Ranolewo, located in the Toraget Village, North Langowan District, North Sulawesi, is recognized for its geothermal manifestation in the form of hot springs, indicating the area's geothermal potential. The aim of this study is to characterize the fluid type of the hot spring manifestation in Ranolewo using geochemical methods. The findings reveal a temperature of 52°C at the manifestation site, with a pH level of 5.6, indicating acidic properties. The fluid type identified in the Ranolewo hot spring area is sulfate water. This is attributed to chemical analysis results showing sulfate as the dominant element, along with the presence of SO4 gas. Sulfate water typically forms at shallow depths due to the condensation of geothermal gases nearing the surface. Geothermal gases, comprising air and carbon, are generally dissolved within fluid content in deeper zones but separated from chloride water. Sulfate water is commonly found at the boundary area, not far from the main upflow zone.